Morphological Study of the Oesophagus and Stomach of the Cave Swiflets (Collocalia linchi) - Savitri Novelina; Evalina E; Aryani S Satyaningtijas; Srihadi Agungpriyono; Heru Setijanto (Jurnal Kedokteran Hewan, 2009)
This study was conducted with aim to tend out morphology of oesophagus and stomach of the cave swiflets (Collocalia linchi) at macroscopic and microscopic levels.  The data revealed that esophagus was 2.93 cm in length and possessed no crop.  The stomach was small and the isthmus was not clear. Mucosa of the esophagus was lined by stratified squoamus epithelium. Esophageal gland was mucous type. The glands were well developed and distributed along the esophagus. The external muscle layer consisted of inner circular and outer longitudinal layers.  The stomach could be distinguished into proventriculus and ventriculus with no clear isthmus between them. The mucosa of proventriculus was lined by single columnar epithelium. The ventricular gland area was divided into cardiac, fundic  and pyloric gland areas. The surface of ventriculus was lined with cuticula. In general the esophagus and stomach of the cave swiftlets were simple with no crop in the esophagus and isthmus in the stomach. These might be related with the kind of food and feeding behavior of this species.